2021
DOI: 10.1371/journal.pone.0253414
|View full text |Cite
|
Sign up to set email alerts
|

Habituation to thaxtomin A increases resistance to common scab in ‘Russet Burbank’ potato

Abstract: Common scab is a potato disease characterized by the formation of scab-like lesions on the surface of potato tubers. The actinobacterium Streptomyces scabiei is the main causal agent of common scab. During infection, this bacterium synthesizes the phytotoxin thaxtomin A which is essential for the production of disease symptoms. While thaxtomin A can activate an atypical programmed cell death in plant cell suspensions, it is possible to gradually habituate plant cells to thaxtomin A to provide resistance to let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Treatment of potato tuber slices with TA induces a dark brown coloration of the parenchyma tissue that is commonly thought to be due to necrosis ( Figure 1 ) [ 14 , 17 , 18 , 21 , 38 ]. Since TA is the main pathogenicity factor of the common scab causative agent S. scabiei , this TA test has often been used to determine the level of sensitivity of different potato varieties to this disease [ 14 , 16 , 17 , 18 ]. However, our results indicated that the intensity of the browning response induced by TA did not correlate with the level of susceptibility to common scab resistance of the RB and YG potato varieties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment of potato tuber slices with TA induces a dark brown coloration of the parenchyma tissue that is commonly thought to be due to necrosis ( Figure 1 ) [ 14 , 17 , 18 , 21 , 38 ]. Since TA is the main pathogenicity factor of the common scab causative agent S. scabiei , this TA test has often been used to determine the level of sensitivity of different potato varieties to this disease [ 14 , 16 , 17 , 18 ]. However, our results indicated that the intensity of the browning response induced by TA did not correlate with the level of susceptibility to common scab resistance of the RB and YG potato varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds synthesised in response to TA can be incorporated in the biopolymer suberin, which is a central component of the potato tuber periderm that forms the main barrier against pathogens [ 42 , 43 ]. Thickening of the tuber periderm and lenticel suberization have been reported in response to S. scabiei and TA, and in common scab resistant somaclones regenerated from TA-selected cells, suggesting that accumulation of phenolics may increase resistance to the disease [ 16 , 28 ]. Phenol accumulation was more important in the RB variety than in YG, suggesting that the strong induction of the phenylpropanoid pathway in RB tubers may contribute to producing a thicker suberin-enriched layer for tuber protection against S. scabiei [ 32 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen days after inoculation, mini tubers were rinsed in water, left to dry, and rated for disease severity. The percentage of surface area covered by necrotic lesions was utilized to evaluate the scab index as follows: 0 = no scab; 0.5 = less than 1%; 1 = 1 to 5%; 2 = 6 to 10%; 3 = 11 to 25%; 4 = 26 to 50%; 5 = 51 to 75%; and 6 = 76 to 100% tuber surface coverage (Beaudoin et al, 2021). The percentage of scab severity index was calculated for each tested isolate as follows:…”
Section: Virulence Assays Of Selected S Scabies Isolates: Common Scab...mentioning
confidence: 99%